HUBUNGAN JUMLAH FOLIKEL ANTRAL DENGAN RESPONS OVARIUM TERHADAP STIMULASI OVULASI - Adnyana, IB Putra (journal of internal medicine; Vol. 7, No. 3 September 2006)
Recent studies show there is possibility to predict ovarian response to ovulation stimulation. Several possible predictor factors are age, ovarian volume, antral follicle count (AFC), ovarian stroma blood flow, and hormonal markers like Follicle Stimulating Hormone (FSH), Estradiol (E2) and Inhibin B. AFC is a simple examination for ovarian reserve. Compared with hormonal markers, AFC more simply, relatively less costly and only using ultrasound machine, which widely available and the result could be obtained in timely manner. To understand relationship between AFC and ovulation stimulation response. All women who joined IVF program with short protocol stimulation from January 2005 until May 2006 were enrolled into the study. Data collected were AFC day two, mature follicle count, total oocyte count, mature oocyte count, and total gonadotrophin dose. Data were analyzed with Kendall’s correlation test to show relationship. This study shows statistically significant correlations between AFC with mature follicle count (r=0,329; p=0,037), total oocyte count (r=0,506; p=0,001), mature oocyte count (r=0,492; p=0,002), and total gonadotrophin dose (r=-0,477; p=0,002). This study shows there are statistically significant correlations between AFC with ovarian response to ovulation stimulation and the cutoff point of AFC is 4,5.
Keywords: Antral Follicle Count, ovarian response, ovulation stimulation, short protocol